Polyoma viruses with mutations at endonuclease HindII site 1: alterations at the COOH terminus of VP1. - Bendig, M M (1979)
Four mutants of polyoma virus lacking endonuclease HindII site 1 were isolated and characterized with respect to the VP1 coding sequence. Three of these mutants had deletions that removed 0.2 to 0.3% of the genome. All three deletion mutants encoded VP1 proteins that were smaller than wild type and that lacked one or more tryptic peptides normally found in the wild-type VP1 protein. Our results suggest the HindII site 1 is at, or very near, the carboxy terminal end of the coding sequence for VP1. A model for the peptide organization in that region is presented.